Environmental significance of Ophiomorpha in a transgressive–regressive sequence of the Spitsbergen Paleocene - Jenȍ Nagy; Francisco J. Rodríguez Tovar; Matías Reolid (Polar Research, 2016)
The study focuses on occurrences of Ophiomorpha burrows in a transgressive–regressive succession composing the Early Paleocene Firkanten Formation deposited in paralic, prodelta to delta front conditions in the Central Basin of Spitsbergen. The burrows colonize sandstones of the Todalen Member at four sites and belong to two ichnospecies: Ophiomorpha cf. nodosa, forming dominantly vertical shafts; and O. cf. irregulaire, consisting of horizontal sinuous tunnels ending in subconical shafts. Both species are observed in shoreface sandstones deposited as a barrier bar. Lithological features and stratigraphic positions suggest that the trace-makers preferentially colonized high-energy sand environments. Foraminiferal faunas occurring below and above the barrier sandstones indicate brackish water conditions for the Ophiomorpha levels, which accordingly are of restricted, monospecific nature. It is inferred that the trace-makers had a dominantly suspension feeding habit as a modern analogue Calianassa major. Portrayed in a sequence stratigraphic framework, the Ophiomorpha-bearing sandstones in middle reaches of the Central Basin were deposited in the final stage of the transgressive systems tract, which drowned the underlying coal-bearing paralic facies. Moreover, in the northern, coal-rich parts of the basin, occurrence of Ophiomorpha signals marine ingression into the paralic system.